Convergence and Self-Help Groups: Conduits for advancing gender equality and social inclusion in agri-food systems - Munshi, Sugandha; Kumar, Ashok; Kumar, Virender (International Rice Research Institute, 2023)
Globally, women are dominantly employed in the agriculture food systems, which is a critical source of livelihood for women as compared to men. As a result, it becomes crucial to brainstorm, design and innovate strategies and approaches that are gender responsive and equally create a conducive platform for transformative agri-food systems. The role of social capital and the local/traditional system becomes critical to have a sustainable approach toward achieving the goal of an inclusive agriculture system where women have an equal and level playing field to that of men. There is an intrinsic need for leveraging platforms that help in dealing with gender power relations and establishing an institutional approach toward systemic change. Critically examining and understanding the role of social innovations primarily including collective actions and institutionalizing changes through two projects interventions Cereal Systems Initiative for South Asia and Precision direct-seeded rice-based diversified systems for transforming labor requirement, yields and profitability of smallholder farmers in Odisha (DSR-Odisha), two innovative approaches that have played a critical role in creating a pathway for genderresponsive agri-food systems—working with women self-help groups (WSHGs) through livelihood missions and institutionalizing the convergence platform. A detailed strategy developed created an inclusive pathway in outreach. Evidence generations were carried out through mixed-methods approaches—both qualitative and quantitative. The convergence platform is a unique innovation and now is institutionalization under the ICAR-ATARI. The platform has been playing a decisive role as far as the inclusive advisories outreach is concerned in eastern India.